2006
DOI: 10.4049/jimmunol.177.4.2717
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous CD4+ T Cell Responses against TRAG-3 in Patients with Melanoma and Breast Cancers

Abstract: The taxol resistance gene TRAG-3 was initially isolated from cancer cell lines that became resistant to taxol in vitro. TRAG-3 is a cancer germline Ag expressed by tumors of different histological types including the majority of melanoma, breast, and lung cancers. In the present study, we report that patients with stage IV melanoma and breast cancers developed spontaneous IFN-γ-producing CD4+ T cell responses against a single immunodominant and promiscuous peptide epitope from TRAG-3 presented in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…They also did not generate a huge number of T cell lines when pools of peptides were used as immunogens, suggesting that either these T cells are not able to be expanded or that our culture conditions are not appropriate for their expansion. Spontaneous CD4 T cell responses to the cancer Ag OCT4 or MUC-1 have already been observed in healthy donors (43,44), but remained unusual as compared with other tumor Ags (8,11,12,45,46). For the first time, to our knowledge, we demonstrated that the spontaneous CD4 T cell response to CCNB1 persists in cancer patients and is not therefore dampened by the tumors.…”
Section: Discussionmentioning
confidence: 71%
“…They also did not generate a huge number of T cell lines when pools of peptides were used as immunogens, suggesting that either these T cells are not able to be expanded or that our culture conditions are not appropriate for their expansion. Spontaneous CD4 T cell responses to the cancer Ag OCT4 or MUC-1 have already been observed in healthy donors (43,44), but remained unusual as compared with other tumor Ags (8,11,12,45,46). For the first time, to our knowledge, we demonstrated that the spontaneous CD4 T cell response to CCNB1 persists in cancer patients and is not therefore dampened by the tumors.…”
Section: Discussionmentioning
confidence: 71%
“…We and others have previously shown that CGA-derived epitopes that represent tumor-specific T cell targets (27), give rise to spontaneous Th1-type CD4 + T cells isolated either from PBLs or TILs of cancer patients (24,28). However, such spontaneous CD4 + T cell responses are found in patients with progressive disease, questioning their role in promoting potent antitumor CTL functions.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously reported that two immunodominant epitopes derived from the two CGAs, TRAG-3 34-48 and NY-ESO-1 119-143, stimulate spontaneous CD4 + T cells in the majority of patients with NY-ESO-1-expressing and/or TRAG-3-expressing melanoma (21,23,24). Using in vitro stimulation with peptides, we have previously isolated TRAG-3-specific CD4 + T cell clones (i.e., clones 61/58, 62/3, and 62/8) and NY-ESO-1-specific CD4 + T cell clones (i.e., clones 30/79, 35/67, and 11/4) from PBLs of two MPs and two HDs.…”
Section: Resultsmentioning
confidence: 99%
“…We have cloned and sequenced the TCR CDR3␤ regions of each cross-reactive clone as previously reported (28,29) and described in Materials and Methods. Each of the two NY-ESO-1-specific CD4 ϩ T cell clones exhibited a distinct CDR3␤ region involving distinct V␤ and J␤ chains, named CDR3␤ 11/4 (SFYICSAQ-GLAYEQYFGPGTR:V␤2.1-NDN-J␤2.7) and CDR3␤ 30/79 (VYFCASSPGRVSLSGANVLTFG: V␤9-NDN-J␤2.6), respectively.…”
Section: Ex Vivo Detection Of Cross-reactive Tcr From Pbls Of Stage Imentioning
confidence: 99%